Is peer-to-peer electricity trading empowering users? Evidence on motivations and roles in a prosumer business model trial in Australia. (August 2020) - Wilkinson, Sam; Hojckova, Kristina; Eon, Christine; Morrison, Gregory M.; Sandén, Björn
Highlights: First real-world trial of P2P electricity trading within a regulated market. Applies transition and innovation perspectives on users in an early P2P market. Trial participants wish to facilitate learning and co-create the future P2P market. Intermediaries and activists are required to cross the chasm to wide diffusion. Abstract: Peer-to-peer (P2P) electricity markets have attracted significant attention as a promising model enabling the integration of distributed energy sources by creating consumer-based electricity markets. Despite the significance of users in this model, knowledge is still lacking as to who the users interested in P2P electricity markets are and what role they can play in building them. We aim to fill this knowledge gap by providing evidence from the first real-world trial of a P2P electricity market facilitated by blockchain technology across a regulated electricity network. We apply sustainability transition and innovation thinking to analyse the trial participants as users shaping the P2P-related innovation process. Supported by our empirical results, we found that users joined the P2P market trial to learn and co-create the future of prosumer-centred electricity markets. We also found that if P2P is to enter the mainstream market, the assistance of other actors (e.g., intermediaries and activists) is important in order to cross the chasm to reach the majority of users and move from a learning and probing phase to breakthrough and wide diffusion.